2014
DOI: 10.1016/j.ejim.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Management of nontuberculous mycobacterial infection in the elderly

Abstract: The incidence of nontuberculous mycobacteria (NTM) has increased over the last decades. Elderly people are more susceptible to NTM and experience increased morbidities. NTM incidence is expected to rise due to an increasing elderly population at least up to 2050. Given the importance of NTM infection in the elderly, an increasing interest exists in studying NTM characteristics in aged population. In this review, we summarize the characteristics of NTM infection among elderly patients. We focus on epidemiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 110 publications
(113 reference statements)
1
37
0
Order By: Relevance
“…Immunocompromised patients are particularly vulnerable and develop disseminated disease. Other known risk factors include cystic fibrosis, chronic obstructive pulmonary disease (COPD), silicosis, and alpha-1 antitrypsin deficiency [7-12]. Recent studies have also found an association between non-CF bronchiectasis and non-tuberculous mycobacterial infections [13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunocompromised patients are particularly vulnerable and develop disseminated disease. Other known risk factors include cystic fibrosis, chronic obstructive pulmonary disease (COPD), silicosis, and alpha-1 antitrypsin deficiency [7-12]. Recent studies have also found an association between non-CF bronchiectasis and non-tuberculous mycobacterial infections [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of clinical data, we found that patients with the Type II genotype tended to be younger than those with the Type I genotype. Evidence that increasing age is one of the most important risk factors of NTM infections (25)(26)(27)(28), supports the higher virulence potential of the Type II genotype over Type I. Generally, a pronounced difference is found in treatment success between M. abscessus subspecies, particularly between M. abscessus and M. massiliense.…”
Section: Discussionmentioning
confidence: 85%
“…The incidence of infections resulting in significant mortality and morbidity rates has increased over the past decade (3). Moreover, their incidence is expected to increase until 2050, given the growing geriatric population and higher prevalence of nontuberculous mycobacterial infections among this population (4).…”
Section: Introductionmentioning
confidence: 99%